2017
DOI: 10.22373/psikoislamedia.v2i1.1826
|View full text |Cite
|
Sign up to set email alerts
|

Pendidikan Karakter ‘Tidak Merokok’ Di Sekolah Muhammadiyah Di Kota Kretek

Abstract: ABSTRAKMendidik siswa untuk tidak merokok merupakan salah satu tujuan dari pendidikan karakter di Sekolah. Penelitian ini bertujuan untuk menggambarkan bagaimana pendidikan karakter tidak merokok di sekolah muhammadiyah di Kota Kudus. Peneliti memilih sekolah Muhammadiyah dan bertempat di Kudus, dengan berbagai alasan. Kota Kudus dikenal dengan sebutan Kota kretek, sedangkan Majelis Tarjid dan Tajdid Muhammadiyah mengeluarkan hukum haram bagi orang yang merokok. Selain itu, industri rokok di Kudus juga menduku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The teacher has a role to educate his students in school, including not to smoke. 24 However, based on this study, there is no relationship between the teacher's roles in adolescent smoking behavior. This is possible because of the surrender of the teacher that after school that is in the house handed over to their parents.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The teacher has a role to educate his students in school, including not to smoke. 24 However, based on this study, there is no relationship between the teacher's roles in adolescent smoking behavior. This is possible because of the surrender of the teacher that after school that is in the house handed over to their parents.…”
Section: Resultsmentioning
confidence: 59%
“…This is possible because of the surrender of the teacher that after school that is in the house handed over to their parents. 24 In addition to teachers, the extra-curricular provided in schools has an effect on adolescent smoking behavior. Therefore, promotive efforts are needed in schools to improve students' understanding of the dangers of smoking, such as through school health units and youth school red bars.…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that the teachers might experience a contradictory feelings about the strict smoking prohibition at schools as those cigarette companies have a significant role in that school. Meanwhile, Fatwa Haram on smoking implemented by Majelis Tarjih and Tajdid of Muhammadiyah Central Board does not affect the smoking prohibition in the three said Muhammadiyah Schools in Kota Kretek (Aisah & Ridha, 2017).…”
Section: Introductionmentioning
confidence: 97%